Rural women's knowledge of preventive health in Sidi- Salim district in Kafr El-Sheikh Governorate - Al-Abd, Rabab Ahmed; Ibrahim, Mayada Al-Shawadfy Awad (Journal of agricultural, environmental and veterinary sciences, 2022)
The research aimed to identifying rural women's knowledge about preventive health, identify the relationship between the degree of rural women's knowledge about preventive health and independent variables, identify the contribution of each of the independent variables in variation in the degree of rural women's knowledge about preventive health, and identify the sources of information for rural women about preventive health. The study was conducted on a sample of 322 families from the villages of Al-Salihat and Taida, Sidi Salem district, Kafr El-Sheikh Governorate. Data were collected from the housewife using a personal interview questionnaire, frequencies, percentages, mean, simple correlation coefficients, stepwise multiple linear regression coefficient Used in data presentation and analysis.The main results were as follows:- 65.8% of rural women have an average knowledge of preventive health.- There is a positive relationship between the degree of rural women's knowledge about preventive health and each age, number of family members, housing condition, housing holdings, degree of benefit from cultural openness, information sources, level of ambition, and degree of participation in health-related activities.- Five variables contribute significantly to explaining 47% of the variance in the degree of rural women knowledge about preventive health.- Traditional sources such as (mother and mother-in-law) ranked first, while (personal experience) ranked second as a source for obtaining health-related information.
Keywords: knowledge; rural women; preventive health measures; (health- nutritional- vaccinations)